2018
DOI: 10.1111/apt.15057
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination for influenza and pneumococcus in patients with gastrointestinal cancer or inflammatory bowel disease: A prospective cohort study of methods for improving coverage

Abstract: Summary Background Although influenza and pneumococcal vaccinations for high‐risk populations are recommended by current guidelines, vaccination coverage is low in patients with gastrointestinal cancer (GC) or inflammatory bowel disease (IBD). Aim To evaluate the impact of a specialised infectious disease consultation on vaccination coverage rates in these patients. Methods Between December 2016 and April 2017, all patients with GC or IBD followed in the outpatient clinic of the Gastroenterology department at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Vaccination among adults including those older than 65 years has been shown to be efficient [40]. Healthcare professionals, cancer societies, and other societies advocate for increasing this vaccination rate, which some vaccination programs increased successfully [36]. Cardiovascular diseases are the leading cause of mortality of diabetic patients [41], which may explain the lack of a signal due to diabetes mellitus in our model.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Vaccination among adults including those older than 65 years has been shown to be efficient [40]. Healthcare professionals, cancer societies, and other societies advocate for increasing this vaccination rate, which some vaccination programs increased successfully [36]. Cardiovascular diseases are the leading cause of mortality of diabetic patients [41], which may explain the lack of a signal due to diabetes mellitus in our model.…”
Section: Discussionmentioning
confidence: 96%
“…A recent French study showed a 10% rate among patients with comorbidities at risk [12]. A single-institution study focusing on 99 patients with gastrointestinal cancer yielded a pneumococcal vaccination rate of 10.1% (95% CI [4.1-16]) [36]. As shown in several studies, childhood vaccination programs contribute to herd immunity, thus partly protecting non-vaccinated adults [37,38].…”
Section: Discussionmentioning
confidence: 98%
“…A prospective cohort study evaluating the impact of a specialized infectious disease consultation on vaccination coverage rates in patients with gastrointestinal cancer or IBD showed this consultation could significantly improve patients’ knowledge about vaccination and vaccination coverage [ 17 ]. This approach could be applied to improve COVID-19 vaccination in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The other 3 studies [33 , 37 , 47] also utilized education (in the form of written educational form [33] , education by the IBD nurse with help of an information brochure and vaccination card [37] , and vaccination educational update by an infectious disease specialist [47] ) to improve the vaccination rate. The study by Sitte et al [47] recruited patients with gastrointestinal cancer (GC) or IBD.…”
Section: Intervention To Improve Vaccination Ratementioning
confidence: 99%
“…The other 3 studies [33 , 37 , 47] also utilized education (in the form of written educational form [33] , education by the IBD nurse with help of an information brochure and vaccination card [37] , and vaccination educational update by an infectious disease specialist [47] ) to improve the vaccination rate. The study by Sitte et al [47] recruited patients with gastrointestinal cancer (GC) or IBD. There was significant improvement in vaccination rate: in GC patients, pneumococcal vaccination rate increased from 10.1% to 87.5% after the specialized consultation, whereas the corresponding rates were 16.1% and 85.7%, respectively, for IBD patients.…”
Section: Intervention To Improve Vaccination Ratementioning
confidence: 99%